A snapshot of intraoperative conditions to predict prolonged postoperative ileus after colorectal surgery. Issue 9 (17th May 2022) - de Gaay Fortman, Duveke P. E.; Kroon, Hidde M.; Bedrikovetski, Sergei; Fitzsimmons, Tracy R.; Dudi‐Venkata, Nagendra N.; Sammour, Tarik
Abstract: Background: The cause of prolonged postoperative ileus (PPOI) is multifactorial. The influence of preoperative factors on PPOI has been well documented, but little is known about the impact of intraoperative conditions. The aim of this study was to investigate the influence of intraoperative factors on PPOI in patients undergoing colorectal surgery. Methods: The LekCheck study database of the Colorectal Unit at the Royal Adelaide Hospital was analysed. Per patient, over 60 data points were prospectively collected between March 2018 and July 2020. Intraoperative data were collected in theatre during a one‐off snapshot measure. Univariate and multivariable logistic regression analyses were performed. Results: Data of 336 patients were included. The median age was 66 years and 58.3% were male. Ninety‐three patients (27.7%) developed PPOI. Univariate analysis identified the following intraoperative variables as risk‐factors of PPOI: greater volumes of intraoperative IV fluid administration (464 versus 415 mL/h for those without PPOI; p = 0.04), side‐to‐side anastomosis orientation (53.8 versus 41.2%; p = 0.04) and increased perioperative opioid use (6.73 versus 4.11 mg/kg morphine equivalents for patients with and without PPOI, respectively; p = 0.02). Upon multivariable analysis, increased perioperative opioid use remained significant ( p = 0.05), as well as the preoperative factors anticoagulation use ( p = 0.04) and higher levels of serum total protein ( p = 0.02). Conclusion: This study suggests that intraoperative factors may also contribute to the development of PPOI, but this could not be confirmed in the multivariate analysis. Further studies including larger patient numbers will be required to determine the impact of intraoperative conditions on the development of PPOI. Abstract : The influence of preoperative factors on PPOI has been well documented, but little is known about the impact of intraoperative conditions. This study collected intraoperative data during a one‐off snapshot measure. We suggests that intraoperative conditions may contribute to the development of PPOI, but this could not be confirmed in the multivariate analysis.